The densification of second home areas — sustainable practice or speculative land use?. (July 2022) - Hjalager, Anne-Mette; Staunstrup, Jan Kloster; Sørensen, Michael Tophøj; Steffansen, Rasmus Nedergård
Abstract: UN Sustainable Development Goal #11 prescribes a much more careful territorial planning and land use control. This study documents second homes' land use from this perspective, considering higher built-up density as a measure to limit land-take. The quantitative study includes public property data on all second homes in Denmark. A concise account of the 180, 000 properties demonstrates a tendency towards densification, measured as an increase in the amount of built space on the existing land sites. Over time, the average house size increases, an expression of improved living quality. Incentive for owners are the rising second home market prices and the opportunities for creating profitable ownership by offering the property on the touristic renting market when they do not use it themselves. The sustainability-motivated appeal for densification coincides with the speculative land use intensification. The dual agenda is backed by the tourism lobby and policymakers. The downside of densification is the simultaneous underprioritizing of other important sustainability goals, such as biodiversity, the preservation of landscape values, human wellbeing, etc. Following a public debate about unintended side effects of densification, there seems to be an emerging discussion about the needs to move from a very liberal multilevel planning model for second home areas towards a more firm and transparent planning practice. This corresponds with the recommendations in the SDGs. Highlights: The study maps land use density in Danish second home zones, and it estimates remaining building capacity. The second home capacity can be expanded considerably with no net land take through densification. The regional variance of property value suggests underlying speculative land use intensifications. SDGs can guide planning, but there are concerns for amenity values, the environment, and economy clashes. Planning visions and instruments need adjustment in order to advance principles expressed in SDGs.